VD_FINDINFO HC / 2013 / 668 vom 9. Oktober 2013 - VD Tribunal cantonal (2013)
SUSPENSION DE LA PROCÉDURE, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 126 al. 2 CPC (CH), 319 let. b ch. 1 CPC (CH), 53 al. 1 CPC (CH)